1998
DOI: 10.1002/(sici)1096-9861(19981123)401:3<395::aid-cne7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of glucocorticoid receptors in the forebrain of the rainbow trout (Oncorhynchus mykiss)

Abstract: The distribution of glucocorticoid receptor-expressing cells was studied in the forebrain of the rainbow trout by means of antibodies produced against a fusion protein made of the NH2-terminal fragment of the rainbow trout glucocorticoid receptor fused in frame with glutathione-S-transferase. The results indicate that glucocorticoid receptor-expressing cells are located in many brain regions from the telencephalon to the spinal cord, with the highest density in the neuroendocrine component of the brain, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 67 publications
9
27
1
Order By: Relevance
“…Sandor et al 1984, Weisbart et al 1984, Maule & Schreck 1990, Pottinger & Moore 1997, Weyts et al 1998, Marsigliante et al 2000, and full-length glucocorticoids receptor (GR) cDNAs (rainbow trout (Oncorhynchus mykiss): Ducouret et al (1995), Takeo et al (1996); Japanese flounder, Genbank ABO1344) and a partial tilapia GR cDNA (Tagawa et al 1997) have been cloned. Expression of rainbow trout GR (rtGR) transcript is found in a number of tissues (Ducouret et al 1995, Takeo et al 1996, is widely distributed in the brain (Teitsma et al 1997(Teitsma et al , 1998 and has been identified in gill chloride cells (Uchida et al 1998), the cells believed to be responsible for branchial ion movement (Perry 1997). Despite the absence of aldosterone in fish, a recent study identified a partial cDNA sequence of a corticosteroid receptor in rainbow trout, whose amino acid sequence showed a high homology with known mineralocorticoid receptors (MRs).…”
Section: Introductionsupporting
confidence: 92%
“…Sandor et al 1984, Weisbart et al 1984, Maule & Schreck 1990, Pottinger & Moore 1997, Weyts et al 1998, Marsigliante et al 2000, and full-length glucocorticoids receptor (GR) cDNAs (rainbow trout (Oncorhynchus mykiss): Ducouret et al (1995), Takeo et al (1996); Japanese flounder, Genbank ABO1344) and a partial tilapia GR cDNA (Tagawa et al 1997) have been cloned. Expression of rainbow trout GR (rtGR) transcript is found in a number of tissues (Ducouret et al 1995, Takeo et al 1996, is widely distributed in the brain (Teitsma et al 1997(Teitsma et al , 1998 and has been identified in gill chloride cells (Uchida et al 1998), the cells believed to be responsible for branchial ion movement (Perry 1997). Despite the absence of aldosterone in fish, a recent study identified a partial cDNA sequence of a corticosteroid receptor in rainbow trout, whose amino acid sequence showed a high homology with known mineralocorticoid receptors (MRs).…”
Section: Introductionsupporting
confidence: 92%
“…In teleosts, cortisol can act as a mineralocorticoid and glucocorticoid, targeting both glucocorticoid receptor(s) (GR) and mineralocorticoid (Arai, Assil et al) receptors(s) (Knoebl, Fitzpatrick et al 1996;Teitsma, Anglade et al 1998;Greenwood, Butler et al 2003;Sturm, Bury et al 2005). Under normal circumstances, cortisol release is associated with stress, gluconeogenisis, metabolic function, immune suppression, and osmoregulation in several species of fish.…”
Section: Understanding the Role Of Chronic Stress Response In Semelpacontrasting
confidence: 78%
“…Moreover, we provide novel evidence that the negative feedback effects of cortisol on plasma ACTH can persist for at least 8 days beyond the return of cortisol to baseline levels. In contrast, although cortisol has been shown to decrease POA crf gene expression in a few fish species (reviewed by Bernier et al 2009), and NPO CRF immunoreactive neurons co-express GRs in rainbow trout (Teitsma et al 1998), chronically elevated cortisol levels in this study were associated with a sustained increase in POA crf mRNA levels. Similarly, suppression of GR signaling in rainbow trout using the GR antagonist RU486 reduces POA crf mRNA levels (Doyon et al 2006, Alderman et al 2012.…”
Section: Discussionmentioning
confidence: 99%